Implementation barriers to management accounting practices in the Malaysian public sector - A. K. Siti-Nabiha; Noriza Mohd Jamal; Rozaidy Mahadi (Centre for Professional Development (IPNCPD) National Accounting Institute, 2024)
Purpose: This study seeks to examine implementation barriers to management accounting reporting in the Malaysian public sector. Design / Methodology / Approach: A qualitative approach was utilized, wherein interviews were conducted with both accountants and non-accountants in two ministries and the Accountant General’s Department of Malaysia (AGD). In addition, documentary reviews related to the management accounting reporting framework and guidelines were analysed. Findings: Implementation barriers related to the current management accounting reporting and analysis were categorised into three primary domains, namely cognitive, technical, and organisational. Cognitive barriers refer to the mindset of accountants and non-accountants about the instrumentality of management accounting reports and the underlying budgetary philosophy of the Malaysian public sector. The organisational barriers are related to coordination among different parties involved due to the fragmentation in managing processes and rules and regulations of management accounting reporting. Meanwhile, technical barriers are defined as insufficient integrated system support in management accounting software, hardware, components, and elements. Originality / Value: The present study contributed significant insights into the implementation barriers to the management accounting reporting framework by the Malaysian central government.